Parallel implementation of explicit 2 and 3-point block methods for solving system of special second order ODEs directly - Yap, Lee Ken; Ismail, Fudziah; Abdul Majid, Zanariah; Othman, Mohamed (Universiti Putra Malaysia Press, 2011)
In this paper the explicit 2 and 3-point block method for solving large systems of special second order ODEs directly is discussed. Codes based on the methods are executed in sequential and parallel. The numerical results show that parallel to sequential counterpart for solving the large system of special second order ODEs.